Clinical and Molecular Characterization of Thai Patients with Wiskott–Aldrich Syndrome. (26th December 2012) - Amarinthnukrowh, P.; Ittiporn, S.; Tongkobpetch, S.; Chatchatee, P.; Sosothikul, D.; Shotelersuk, V.; Suphapeetiporn, K.
Abstract Wiskott–Aldrich syndrome (WAS) is an X‐linked recessive primary immunodeficiency disorder caused by mutations in the gene encoding the WAS protein (WASP). Classic WAS is characterized by thrombocytopenia with small‐sized platelets, recurrent infections, eczema and increased susceptibility to autoimmune diseases and haematologic malignancies. Here, we reported on seven unrelated Thai individuals with classic WAS. In addition to clinical and immunologic characterization, mutation analysis by PCR‐sequencing the entire coding region of WASP was performed. Recurrent and novel mutations were successfully identified. A nonsense mutation, the c.55C>T (p.Q19X), has not been previously described, expanding the mutational spectrum of WASP. The patient with this newly described mutation developed cow's milk allergy manifesting as angioedema and urticaria and had cytomegalovirus infection that was successfully treated with long‐term ganciclovir. This study reported long‐term follow‐up of seven patients with molecular confirmation of WAS and infrequent features in the patient with classic WAS carrying the novel nonsense mutation.